Analysis of the sunset equatorial ionosphere using absorption data - Nathaniel, Ekong; Thomas, Jewel; Akpan, samuel (IJRDO-Journal of Applied Science, 2020)
The absorption of a radio waves transmitted obliquely from a transmitter located at a distance about 110km in Cotonou from Lagos has been investigated. The absorption has been determined for a signal that was received on a tuned frequency of about 4.9MHz. The useful parameters for the determination of absorption have been obtained from manual on ionospheric absorption measurements. The results have been based on the post sunset data which have been calculated for different days.